Differences in Tendon Graft Healing Between the Intra-articular and Extra-articular Ends of a Bone Tunnel - Bedi, Asheesh (Springer-Verlag, 2008)
The basic biology of healing between a tendon graft and bone tunnel remains incompletely understood. Distinct variability in the morphological characteristics of the healing tendon–bone attachment site has been reported. We hypothesized that spatial and temporal differences in tendon-to-bone healing exist at different regions of a surgically created bone tunnel. Twenty-four male, Sprague–Dawley rats underwent anterior cruciate ligament (ACL) reconstruction in the left knee using a flexor digitorum longus tendon graft secured using suspensory periosteal fixation. Animals were sacrificed at 4, 7, 11, 14, 21, and 28 days after surgery and prepared for routine histology and immunohistochemical analysis of the healing enthesis at the intra-articular aperture (IAA), mid-tunnel, and extra-articular aperture (EAA). Six animals were used to measure mineral apposition rate (MAR) along the healing bone tunnel by double fluorochrome labeling at 14 and 28 days after surgery. The total area of calcified bone matrix was assessed with von Kossa staining and Goldner-Masson trichrome staining, respectively. The healing tendon–bone interface tissue exhibited a wide chondroid matrix at the IAA, in contrast to a narrow, fibrous matrix at the EAA. There were significantly more osteoclasts at the IAA compared to EAA throughout the study period, except 4 days after surgery (p < 0.05). Collagen continuity between the tendon graft and bone tunnel increased over time, with a more parallel orientation and increased collagen fiber continuity between tendon and bone at the EAA compared to the IAA. MAR was also significantly greater at the EAA at 4 weeks (p < 0.001). Significant differences in healing between the tendon graft and bone exist along the length of bone tunnel secured with suspensory fixation. The etiology of these differences is likely multifactorial in nature, including variable biological and biomechanical environments at different ends of the tunnel. Understanding these differences may ultimately allow surgeons to improve the quality of graft fixation and long-term outcomes after ACL reconstruction.